STUDIO OF ART THERAPEUTIC PRACTICES IN THE CONTEXT OF FORMATION OF SENIOR SCHOOL STUDENTS’ LIFE SUCCESSFULNESS OF - Necherda, Valeriia (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The purpose of the research is to substantiate the potential of art therapy as a means of shaping students’ life successfulness and to present the successful experience of applying art therapy practices in the educational process of experimental institutions of general secondary education. The tasks of the mentioned work are the summarization of data concerning art therapy in educational science and practice, in particular, in the formation of students’ life successfulness and highlighting the features of the structural and organizational focus on the formation of life successfulness of senior school students, which is presented by the studio of art therapy practices «Inimitability». System-structural analysis of domestic and foreign psychological-pedagogical sources regarding the problem of introducing art therapy into the educational process of general secondary education institutions, as well as theoretical generalization, comparison and reinterpretation of the obtained data to formulate the conclusions of the research were chosen as theoretical methods. Empirical methods were the «equal to equal» method, «brainstorming», theatrical games, analysis of situations, discussions, with their assistance art therapy practices were introduced into the process of forming the life successfulness of senior school students. Personally oriented, acmeological and competence approaches became the theoretical and methodological basis of the research. The author outlines indications for art therapy work with senior school students and indicates the maximum correspondence of art therapy to the interests and needs of modern senior school students. The work examines the components of the studio of art therapy practices «Inimitability», namely: the group of theatrical art «Dream»; Folk music factory; Dance school «Impulse»; Club of free and thematic painting; Workshop of art therapy collages and installations; League of sculpting enthusiasts «L in the cube», attention is focused on the educational potential of these practices and various forms of organization of art therapy activities of high school students are defined. The proposed research singles out the main function of art therapy – the function of personality restoration (diagnostic, preventive, psychohygienic, rehabilitation), together with developmental, creative and socializing, and highlights the advantages of art therapy in shaping the life successfulness of senior school students in the conditions of military rule and post-war reality. Based on the obtained results, the growth of the necessity of senior school students for self-determination and achievement of life success, the expansion of the individual and psychological experience of self-realization of students, the implementation of socially significant students’ initiatives, the development of key skills and life-creating abilities of senior school students necessary for life success were noted.